Firms’ Size Moderating Financial Performance in Growing Firms: An Empirical Evidence from Pakistan - Abbasi, Atif; Malik, Qaisar Ali (International Journal of Economics and Financial Issues, 2015)
The main determination of the research is to pinpoint the moderating inspiration of firm size between the relationship of firm growth and firm performance. In the study Null and alternative hypothesis have been constructed, Null hypothesis is concerning the negation of the moderating effect of firm size, while alternative hypothesis is pertaining to the acceptance of the moderating inspiration of firm size between the relationship of firm growth and firm performance. For this purpose, the secondary cross sectional data has been gathered from 50 firms listed in Karachi stock Exchange. Before application of regression equation the formality of stationary of data has been fulfilled, in addition the issue of the multi-co-linearity has also been resolved. The results of the regression analysis are demonstrating that the alternative hypothesis of the research that firm size has moderating inspiration between independent variable (Firm growth) and dependent variable (Firm performance) is accepted. The study is cooperative for the management to keep an eye on firm size along with firm growth while enhancing the firm performance. The future aspects of the research have also been discussed. Keywords: Firm size, Firm growth, Firm performance JEL Classifications: G30, G32, M10